Etiological Correlates of Hoarse Voice - Ranjeet Ranjan; Pushpavathi M. (Journal of All India Institute of Speech and Hearing, 1970)
Hoarse voice is a common voice disorder seen in majority of the clients. Hoarse voice is a symptom in structural and neurological voice disorder. Apart from this it is also seen in developmental voice disorder (puberphonia) and reported more in professional voice users. The present study is an attempt to find the prevalence, etiology spectrum of and pathology related to hoarse voice, based on retrospective design. Sixty eight cases file with voice disorder were reviewed to explore the etiology and pathology. The hoarse voice was prevalent more common in adult males compared to females. The pathology correlated with hoarseness were laryngitis and vocal nodules. Acoustically the fundamental frequency was reduced in 60 patients and normal intensity was seen in all the clients.